Effect of Temperature and Yeast on the Formation of Coumarin in Bakery Ware Containing Mahaleb. A Fully Validated Approach. (15th July 2021) - Krystalli, Evangelia; Komaitis, Efstratios; Thomaidis, Nikolaos; Calokerinos, Antony C.; Proestos, Charalampos
Abstract: Mahaleb, which is a spice with culinary use in Eastern and Mediterranean countries, is a natural source of coumarin. Its presence in bakery ware has not yet been studied, despite the fact that it is widely used in traditional products. In this study, coumarin determination in mahaleb and bakery ware was succeeded employing high-performance liquid chromatography with diode array detection. The method developed was validated under ISO/IEC17025. Coumarin contained in the tested bakeryware ranged from 1.6 to 109 mg/kg. As a result, the permitted limit of 15 mg/kg set by Regulation (EC) 1334/2008 was in some cases exceeded by 7.3-times. The temperature and the baker's yeast effect on coumarin formation was also investigated. Yeast presence showed no effect. On the contrary, high temperature resulted in a maximum 40-fold coumarin formation compared to its initial level. Coumarin's formation was then studied at different baking temperatures (160 ο C and 180 ο C) for different time intervals. Bound coumarin, (defined as coumarin released from its glucosides by acid hydrolysis), was also studied and quantified for the first time in raw mahaleb and bakery ware. The determined average concentration of coumarin in mahaleb was 346 mg/kg, while bound coumarin determined as 90% of total content, reaching in some cases 8800 mg/kg.